Health related quality of life of smokers in Croatia - Samardžić, Senka (Array, 2009)
Summary: The aim of this study was to investigate the health related quality of life (HRQOL) in relation to the smoking status. The data from the Croatian Adult Health Survey conducted in 2003 were used for this study. Sample comprised 9,070 participants, 68.1% women and 31.9% men, from 18 to 101 years old. Results indicated that there were significant differences in HRQOL between smokers and non-smokers even in a young adult age when there is no difference in objective health status (for example diagnosis of disease). Generally health decreased with the age for both groups but direction of difference between smokers and non-smokers varied for different health dimensions across the age groups. The most notable difference in HRQOL in relation to smoking was found in the age group of 65 and older where women smokers reported better HRQOL than non-smokers, and men smokers significantly worse HRQOL than non-smokers. As we found significant differences according to gender in age groups, we suggest that it is essential for future studies to take those characteristics into consideration. Many other factors, for example education, income, marital status, and the socio-cultural acceptability of smoking may have an impact on the quality of life, and also need to be considered in future research. The existing differences in mental health and social functioning should be taken into account in planning of the future prevention programs